Development of Contemporary Ready-to-Wear “Viramrdu” Using Upcycle Denim and Tenun Bulu for Sustainable Fashion - Faza, Najwa Mayla; Krisnawati, Maria (Universitas Negeri Semarang, 2025)
This study examines the development of contemporary ready-to-wear apparel “Viramrdu” by integrating upcycled denim and tenun bulu as an effort to address textile waste issues while preserving traditional Indonesian textiles. The rapid growth of the fashion industry has increased denim waste and reduced the relevance of local textiles in modern fashion, necessitating sustainable and innovative design approaches. This study employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Product feasibility was assessed through expert judgment involving three professional fashion designers using evaluation indicators covering design, size, aesthetics, sewing techniques, fashion performance, and product uniqueness. The findings indicate that the “Viramrdu” ready-to-wear fashhion achieved a “Highly Feasible” category across all assessment indicators, demonstrating strong design quality, proportional sizing, aesthetic value, functional comfort, and innovation in material exploration. The integration of upcycled denim and tenun bulu successfully produced a contemporary, edgy, and functional fashion while maintaining sustainability principles. This study concludes that combining upcycled materials with traditional textiles has significant potential to support the development of sustainable ready-to-wear fashion with a strong design identity and market relevance.